New records of tardigrade species of the Macrobiotus hufelandi group (Tardigrada: Eutardigrada: Macrobiotidae) from Ukraine - Kiosya, Ye.; Shuba, V.; Matsko, Ye. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
Species of the Macrobiotus hufelandi group are among the most well known and commonly found tardigrades. They are reported in almost every study of Tardigrada diversity in terrestrial habitats. In spite of this, zoogeographical data on this group remain ambiguous and insufficient. Since most species of the M. hufelandi group have been described in the last three decades, many older records need to be confirmed or revised. In this study we aimed to investigate, which species may be present in Ukraine, since most Ukrainian records of this group are outdated. We studied samples of mosses and lichens collected from different regions of Ukraine (mainly in the East and South of the country) in 2007–2019. Tardigrades were extracted from samples and mounted on permanent slides in Faure's medium. After primary identification of genera and species groups we focused on 13 samples containing local populations of the M. hufelandi group. Details of animal and egg morphology were studied under high magnifications of phase contrast light microscopy. Species were identified based on morphology of the oral cavity armature, egg shell morphology, animal cuticle granulation, as well as some morphometric characters of claws and bucco-pharyngeal apparatus. This research revealed the presence of at least six different species in Ukraine: M. glebkai Biserov, 1990; M. hufelandi C.A.S. Schultze, 1834; M. macrocalix Bertolani & Rebecchi, 1993; M. polonicus Pilato, Kaczmarek, Michalczyk & Lisi, 2003; M. sottilei Pilato, Kiosya, Lisi & Sabella, 2012; M. vladimiri Bertolani, Biserov, Rebecchi & Cesari, 2011. Three of them: M. macrocalix, M. sottilei, and M. vladimiri are reported in this study from Ukraine for the first time. Adding three more species recorded in earlier studies: M. diversus Biserov, 1990; M. persimilis Binda & Pilato, 1972, and M. sapiens Binda & Pilato, 1984 – gives the total count of at least 9 species of the group in Ukraine. However, according to the recent studies on species complexes the real species diversity is very likely to be higher. Nevertheless, more sampling and obtaining molecular data from different Ukrainian populations of the M. hufelandi group from Ukraine are required.